Three-Dimensional Single-Shot Ptychography - Goldberger, David; Barolak, Jonathan; Durfee, Charles G.; Adams, Daniel E. (2020 Conference on Lasers and Electro-Optics (CLEO), 2020)
We introduce three-dimensional single-shot ptychography (3DSSP). 3DSSP implements a novel algorithm to reconstruct multiple 2D planes of a 3D object. We analyze the technique's performance via numerical simulations, and we demonstrate it experimentally.